Toll-like receptor 2 promotes breast cancer progression and resistance to chemotherapy - Antonino Di Lorenzo; Elisabetta Bolli; Roberto Ruiu; Giuseppe Ferrauto; Enza Di Gregorio; Lidia Avalle; Aurora Savino; Pietro Poggio; Irene Fiore Merighi; Federica Riccardo; Mara Brancaccio; Elena Quaglino; et al. (OncoImmunology, 2022)
Cancer stem cells (CSCs) are the main drivers of disease progression and chemotherapy resistance in breast cancer. Tumor progression and chemoresistance might then be prevented by CSC-targeted therapies. We previously demonstrated that Toll-like Receptor (TLR)2 is overexpressed in CSCs and fuels their self-renewal. Here, we show that high TLR2 expression is linked to poor prognosis in breast cancer patients, therefore representing a candidate target for breast cancer treatment. By using a novel mammary cancer-prone TLR2KO mouse model, we demonstrate that TLR2 is required for CSC pool maintenance and for regulatory T cell induction. Accordingly, cancer-prone TLR2KO mice display delayed tumor onset and increased survival. Transplantation of TLR2WT and TLR2KO cancer cells in either TLR2WT or TLR2KO hosts shows that tumor initiation is mostly sustained by TLR2 expression in cancer cells. TLR2 host deficiency partially impairs cancer cell growth, implying a pro-tumorigenic effect of TLR2 expression in immune cells. Finally, we demonstrate that doxorubicin-induced release of HMGB1 activates TLR2 signaling in cancer cells, leading to a chemotherapy-resistant phenotype. Unprecedented use of TLR2 inhibitors in vivo reduces tumor growth and potentiates doxorubicin efficacy with no negative impact on the host immune system, opening new perspectives for the treatment of breast cancer patients.